The Impact of Parkinson's Disease on Social Communication: An Exploratory Questionnaire Study - Sharma, Saryu; Fleck, Kimberly; Winslow, Sherri; Rothermich, Kathrin (Seminars in Speech and Language, 2023)
Individuals with Parkinson's disease (PD) often show breakdown in the production and interpretation of aspects of social communication. However, there is no current method of assessment for evaluating social communication dysfunction in individuals with PD. The aim of this study was to develop a self-report questionnaire for individuals with PD to identify their social communication skills, and further recognize the impact of PD on social communication. Fifty-one individuals with Parkinson's disease answered 28 survey questions. These questions pertained to emotional expression and perception, social communication, sarcasm/humor, and pragmatic skills. Exploratory factor analysis and reliability analysis were conducted to identify items loading onto the factors and to check the internal consistency of the items. Individuals with PD reported changes in emotional expression and perception, social communication, sarcasm and humor, and pragmatic skill domains post-PD diagnosis. No correlations were found between age or time since diagnosis and emotional expression, social communication, sarcasm, and humor. This study provides self-reported evidence that individuals with PD experience social communication challenges. Future research should further quantify these challenges, study their impact on daily communicative functioning, and use the results to develop social communication interventions that improve the quality of life for persons with PD.
Keywords: Parkinson's disease; social communication; questionnaire; sarcasm; nonliteral; pragmatics